Perancangan Fasilitas Publik Mushola sebagai Penunjang Kegiatan Beibadah Warga Kampung Susun Kunir: Design of a Public Prayer Facility to Support Communal Worship in Kampung Susun Kunir - Permata, Suciati; Christy Vidiyanti; Swasti, Tathia Edra; Hasbi, Rahil Muhammad; Ghassani, Dea Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Kampung Susun Kunir is a vertical housing project for residents relocated from riverbank settlements in Jakarta, who face limitations in access to religious facilities. The existing prayer room (mushola) is makeshift, narrow, and inadequate in terms of capacity, comfort, and environmental sustainability. Spiritual activities such as congregational prayers, study groups, and children's religious education play a vital role in strengthening the community's social cohesion. This community service program aimed to design a permanent, contextually appropriate mosque that accommodates the needs of a dense vertical environment while actively involving residents throughout the planning process. The methodology included needs assessment surveys, site observations, focus group discussions, participatory design workshops, and design validation. The outcomes consist of a complete architectural design of the mushola, a modular prototype adaptable to limited space, a technical guide for construction and community-based management, and documentation of participatory processes. All deliverables were developed to be replicable and directly applicable by residents to fulfill the need for sustainable communal religious facilities. Furthermore, the program contributed to students' experiential learning in real-world settings, enhanced community capacity for public space planning, and strengthened collaboration among universities, local communities, and stakeholders to improve the quality of urban life.